Terminator 3 [videorecording (Blu-Ray)] : rise of the machines - Mostow, Jonathan; Schwarzenegger, Arnold; Stahl, Nick, 1979-; Danes, Claire, 1979- (Warner Bros. Entertainment, 2009)
Now an adult and on his own, John Connor is once again persecuted by a Terminator sent from the future and is protected by the original Terminator, his one time enemy.